Meso-2′-Linked porphyrin–BODIPY hybrids: synthesis and efficient excitation energy transfer1. Issue 35 (21st September 2015) - Hu, Qin-Qin; Zhu, Yi-Zhou; Zhang, Shao-Chun; Tong, Yu-Zhang; Zheng, Jian-Yu
<x xml:space="preserve">Abstract</x> Three meso-2′-linked porphyrin–BODIPY hybrids (BDP–ZnP, 2BDP–ZnP, and 4BDP–ZnP) were synthesized, and fast and highly efficient energy transfer was achieved.